An Amoebal Grazer of Cyanobacteria Requires Cobalamin Produced by Heterotrophic Bacteria - Ma, Amy T; Beld, Joris; Brahamsha, Bianca (Applied and environmental microbiology, 2017)
Amoebae are unicellular eukaryotes that consume microbial prey through phagocytosis, playing a role in shaping microbial food webs. Many amoebal species can be cultivated axenically in rich media or monoxenically with a single bacterial prey species. Here, we characterize heterolobosean amoeba LPG3, a recent natural isolate, which is unable to grow on unicellular cyanobacteria, its primary food source, in the absence of a heterotrophic bacterium, a species coisolate. To investigate the molecular basis of this requirement for heterotrophic bacteria, we performed a screen using the defined nonredundant transposon library of , which implicated genes in corrinoid uptake and biosynthesis. Furthermore, cobalamin synthase deletion mutations in and the species coisolate do not support the growth of amoeba LPG3 on cyanobacteria. While cyanobacteria are robust producers of a corrinoid variant called pseudocobalamin, this variant does not support the growth of amoeba LPG3. Instead, we show that it requires cobalamin that is produced by the species coisolate. The diversity of eukaryotes utilizing corrinoids is poorly understood, and this amoebal corrinoid auxotroph serves as a model for examining predator-prey interactions and micronutrient transfer in bacterivores underpinning microbial food webs. Cyanobacteria are important primary producers in aquatic environments, where they are grazed upon by a variety of phagotrophic protists and, hence, have an impact on nutrient flux at the base of microbial food webs. Here, we characterize amoebal isolate LPG3, which consumes cyanobacteria as its primary food source but also requires heterotrophic bacteria as a source of corrinoid vitamins. Amoeba LPG3 specifically requires the corrinoid variant produced by heterotrophic bacteria and cannot grow on cyanobacteria alone, as they produce a different corrinoid variant. This same corrinoid specificity is also exhibited by other eukaryotes, including humans and algae. This amoebal model system allows us to dissect predator-prey interactions to uncover factors that may shape microbial food webs while also providing insight into corrinoid specificity in eukaryotes.